Numerical Approach for Solving Fractional Integral Equations using Fixed-point Iterative Scheme - Ansar, Ahmad; Fatimah, Meryta Febrilian; Renggawati, Rini (Journal of Mathematics, Computations and Statistics, 2025)
This paper is aimed to solve fractional integral equations using fixed point iterative approach. We used D-plus iteration process with nonexpansive mapping in uniformly convex Banach spaces. We start by prove weak and strong convergence theorems related for nonexpansive mapping and compare convergence rate of some iterative scheme through numerical example. Furthermore, we use this method to prove the existence and estimate the solution of fractional integral equations. The D-plus iterative method shows the good performance in solve fractional integral equations. We also give some example to illustrate main results.